Complete and rapid regeneration of fragments from the upside-down jellyfish Cassiopea - Ostendarp, Malte; Plewka, Julia; Flathmann, Jenny; Tilstra, Arjen; El-Khaled, Yusuf C.; Wild, Christian (Frontiers in Marine Science, 2022)
The upside-down jellyfish Cassiopea increasingly occurs in many (sub-) tropical coastal habitats such as mangrove forests, seagrass meadows, and coral reefs. Its mixotrophic lifestyle and ecophysiological plasticity as well as a high regenerative capacity may be reasons for its success. While the regeneration of umbrella tissue and body structures (i.e. rhopalia and oral arms) was already demonstrated, it remains unclear whether a fully functioning medusa can regenerate from only umbrella tissue. In this study, we thus investigated the regeneration of umbrella fragments over time. We conducted a laboratory experiment for which we used 18 Cassiopea medusae of three different size classes that were cut into two pieces each, one fragment with oral arms and one without. Over a total observation period of 5 weeks, we regularly monitored survival, pulsation behavior, growth and the regeneration pattern of fragments. Findings revealed that 100% of the fragments with oral arms and 88% of the fragments without oral arms survived. Pulsation behavior occurred in all fragments and lasted until the end of the experiment in 94% of all fragments. The umbrella area of fragments without oral arms showed a significantly higher decrease in the first two weeks compared to fragments with oral arms. A complete regeneration of umbrella tissue was observed in all fragments, with and without oral arms alike, and 50% of all fragments even regenerated rhopalia or oral arms as body structures after 33 days. These results suggest an outstanding regenerative capacity of Cassiopea jellyfish after fragmentation. This may contribute to (i) explain the currently observed success of upside-down jellyfish and (ii) extend our knowledge about its regeneration process, which might even act as an asexual reproduction mode in Cassiopea.